2015
DOI: 10.1111/ejn.12919
|View full text |Cite
|
Sign up to set email alerts
|

Role of vasoactive intestinal peptide in the light input to the circadian system

Abstract: The neuropeptide vasoactive intestinal peptide is expressed at high levels in a subset of neurons in ventral region of the suprachiasmatic nucleus (SCN). While VIP is known to be important for the synchronization of the SCN network, the role of VIP in photic regulation of the circadian system has received less attention. In the present study, we found that the light-evoked increase in electrical activity in vivo was unaltered by the loss of VIP. In the absence of VIP, the ventral SCN still exhibited NMDA-evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 85 publications
(97 reference statements)
0
26
0
Order By: Relevance
“…DeWoskin et al (2015) demonstrated that fast GABA signaling likely regulated neuronal output while slow GABA signaling modulated synchrony. VIP has been shown to regulate entrainment at even longer timescales - loss of VIP did not affect the acute response to light of period1 or electrical activity, but it did significantly reduce long-term increases (Vosko et al, 2015). Our model did not include separate effects for GABA and VIP signaling nor did it account for slow-scale changes in the network.…”
Section: Discussionmentioning
confidence: 99%
“…DeWoskin et al (2015) demonstrated that fast GABA signaling likely regulated neuronal output while slow GABA signaling modulated synchrony. VIP has been shown to regulate entrainment at even longer timescales - loss of VIP did not affect the acute response to light of period1 or electrical activity, but it did significantly reduce long-term increases (Vosko et al, 2015). Our model did not include separate effects for GABA and VIP signaling nor did it account for slow-scale changes in the network.…”
Section: Discussionmentioning
confidence: 99%
“…After synthesis by the hypothalamus, VIP is hypothesized to travel via the blood stream through the RPD, and is then stored in the PN. VIP is also known to play crucial roles in regulating the circadian clock (Colwell et al, 2003;Hamnett et al, 2019;Vosko et al, 2015;Vosko et al, 2007) because it is strongly localized in the suprachiasmatic nucleus of the mammalian brain.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of VIP in the LGBd will lead to a corresponding reduction in the binding of VIP to its related receptors, thereby inhibiting the physiological effect of vascular endothelial growth factor on visual development. At the same time, the decrease in VIP reduces the diurnal discharge frequency of neurons, affecting the long-term electrical activity in the suprachiasmatic nucleus of the central system [19,20] and inhibiting electrical transmission between neurons through the VPAC2-mediated cAMP pathway [21], thereby blocking the transmission of information in the visual nervous system. These effects, in turn, accelerate the emergence of amblyopia.…”
Section: Vip Immunohistochemistrymentioning
confidence: 99%